Analyses of chromosome number, nuclear DNA content and RAPD profile in three morphotypes of Pandanus fascicularis Lam. - Panada, K.K.=700 1 Panigrahy, R.K.; Das, A.B.
(Es, En, Pt)
ilus., 48 ref.
Keywords: PANDANUS; NUMERO DE CROMOSOMAS; ADN; ITALIA; RAPD; PANDANUS FASCICULARIS; NOTICIARIO DE RECURSOS FITOGENETICOS